Integrated reliability condition monitoring and maintenance of equipment - Osarenren, John Osarodion (CRC Press, Taylor & Francis Group, 2015)
This text highlights the solutions to the common failures and reliability of equipment in major industries, through an integrated reliability condition monitoring, and maintenance with a technological inheritance model-based program. It relates all operating conditions of a critical cylindrical equipment part (shaft) throughout its life cycle, starting from design through manufacturing to actual equipment service application. The mathematical relationship of a desired operating manufacturing process and work-piece conditions is developed as a system multivariate quality model that relates with its part failure mechanism